The future costs of cancer attributable to excess body weight in Brazil, 2030-2040 - Leandro F. M. Rezende; Thainá Alves Malhão; Rafael da Silva Barbosa; Arthur Orlando Correa Schilithz; Ronaldo Corrêa Ferreira da Silva; Luciana Grucci Maya Moreira; Paula Aballo Nunes Machado; Bruna Pitasi Arguelhes; Maria Eduarda Leão Diogenes Melo (BMC, 2022)
Abstract Background Excess body weight (EBW), herein defined as body mass index (BMI) ≥25 kg/m2, is a well-known modifiable risk factor for cancer and a pivotal vector for growing healthcare costs. We estimated the future (2030) federal direct healthcare costs of cancer in the Brazilian Unified Health System (SUS) attributable to EBW. We also projected direct healthcare costs of cancer that could be potentially saved in 2040, considering counterfactual (alternative) scenarios of population-wide reductions in the BMI to be achievedin 2030. Methods We developed a macrosimulation model by sex using self-reported BMI data in adults ≥ 20 years who relied exclusively on the public health system from the Brazilian National Health Survey (PNS) 2019; relative risks for 12 types of cancer from the World Cancer Research Fund/American Institute Cancer Research (WCRF/AICR) meta-analysis; and nationwide registries of federal direct healthcare costs of inpatient and outpatient procedures in adults ≥30 years with cancer from 2008-2019. We calculated the attributable costs of cancer via comparative risk assessment, assuming a 10-year lag between exposure and outcome. We used the potential impact fraction (PIF) equation and the Monte Carlo simulation method to estimate the attributable costs and 95% uncertainty intervals, considering the theoretical-minimum-risk exposure and other counterfactual (alternative) scenarios of the EBW prevalence. We assessed the cancer costs attributable to EBW, multiplying PIF by the direct healthcare costs of cancer. Results In 2030, 2.4% or US$ 62.8 million in direct healthcare costs of cancer may be attributable to EBW. We projected potential savings of approximately US$ 10.3 to 26.6 million in 2040 by reducing the prevalence of EBW in 2030. Conclusions We estimated high future costs of cancer attributable to EBW in Brazil. Our findings may support interventions and policies focused on the primary prevention of EBW and cancer.